Implementasi Algoritma OCR (Optical Character Recognition) untuk Ekstraksi Informasi dari Citra Struk Transaksi Keuangan - Latifa Khoirani; Rino Ariansyah; Supiyandi Supiyandi (Mars: Jurnal Teknik Mesin, Industri, Elektro Dan Ilmu Komputer, 2024)
This research aims to automate the process of extracting information from financial transaction receipts using Optical Character Recognition (OCR) algorithm. The OCR algorithm is used to recognize characters from digital images of transaction receipts so that information such as date, transaction amount, and other details can be accurately identified. By applying image processing methods, this research successfully demonstrates the effectiveness of the OCR system in overcoming challenges such as varying receipt print quality. This research also offers practical solutions in the form of OCR-based applications that can be used in business environments to improve the efficiency and accuracy of financial transaction data management.